Literasi Media, Literasi Politik, dan Partisipasi Kewarganegaraan Pemilih Pemula di Era Digital - Ridha, Muhammad; Riwanda, Agus (Universitas Negeri Malang, 2020)
This study intended to determine the effect of media literacy and political literacy on the participation of novice voter citizenship in the digital era. This research used a non-experimental ex post facto quantitative approach. A sample of 350 was chosen randomly. Data analysis used path analysis with the help of the SPSS program. The analysis showed that media literacy significantly influences the level of civic participation (0.567). Second, political literacy also significantly influences the level of civic participation (0.664). Third, media literacy has a significant influence on political literacy (0.563). Fourth, simultaneously media literacy and political literacy affect civic participation (0.689). Fifth, political literacy was not significantly proven to moderate the relationship between media literacy and citizenship participation (p = 0.4590 > 0.05). Media literacy and political literacy affected the civic participation of novice voters both partially and simultaneously. The level of media literacy of the novice voters did not trigger a weak or strong relationship between political literacy and the citizenship participation of the novice voters.